In/Ga Inter-Diffusion in InAs Quantum Dot in InGaAs/GaAs Asymmetric Quantum Well - Abdellatif, M. H.; Song, Jin Dong; Choi, Won Jun; Cho, Nam Ki (AMER SCIENTIFIC PUBLISHERS, 2012)
The Photoluminescence spectra (PL), their temperature and power dependence were investigated for the ground state in InAs quantum dots (QDs) embedded in InGaAs asymmetric quantum well (Asym. QW). In-atom segregation is well known phenomena in such structures, which result in altering the inter-atomic distances; as a consequence the thermo-dynamical parameters change as well, namely Debye temperature. The bigger value of Debye temperature for the studied sample with respect to the corresponding bulk value is attributed to In/Ga inter-diffusion during growth. The inter-diffusion process causes non-radiative defects in the sample. As a consequence, rapid decrease in the QDs integrated emission intensity as the temperature increases was occurred.
Keywords: TEMPERATURE-DEPENDENCE; ENERGY-GAP